X-Shaped Alignment of Chromophores: Potential Alternative for Efficient Organic Terahertz Generators - Lee, Ji Ah; Kim, Won Tae; Jazbinsek, Mojca; Kim, Deokjoong; Lee, Seung Heon; Yu, In Cheol; Yoon, Woojin; Yun, Hoseop; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2020)
Efficient broadband organic terahertz (THz) generators using X-shaped alignment of the nonlinear optical chromophores, as an alternative to the parallel alignment of chromophores in benchmark organic crystals, are reported. All the developed six organic benzothiazolium crystals exhibit an isomorphic X-shaped alignment of chromophores, resulting in an unprecedentedly large off-diagonal optical nonlinearity (>100 × 10−30 esu), which presents one of the largest off-diagonal optical nonlinearity of organic crystals. The benzothiazolium crystals exhibit efficient broadband THz wave generation employing the off-diagonal optical nonlinearity, in contrast to the present state-of-the-art organic THz generators that mostly utilize diagonal optical nonlinearity. For using off-diagonal and diagonal optical nonlinearities, the polarization of the optical pump is perpendicular and parallel, respectively, to the polar axis of crystals. In addition to a large THz wave generation efficiency with one order of magnitude higher peak-to-peak THz electric field than that generated in a 1.0-mm-thick inorganic benchmark ZnTe crystal, the benzothiazolium crystals generate broadband THz spectra with an upper cut-off frequency of near 8 THz, and the absence of strong absorption dimples in the range of 0.5−4 THz. Therefore, the X-shaped alignment of chromophores presents an interesting potential alternative for efficient broadband organic THz generators.
Keywords: Nonlinear optical chromophore; Nonlinear optical crystal; Optical nonlinearity; Organic crystal; Parallel alignments; State of the art; Strong absorptions; ZnTe crystal; nonlinear optical crystals; organic crystals; THz generators